Development of Policy and Measure to Use Cannabis for Recreation in Thailand - Vongthip, Vivit (Huachiew Chalermprakiet Law Journal, 2024)
The objective of research is to present the guideline for the recreational cannabis use in Thailand under legal framework. According to the removal cannabis from the list of Narcotic drugs in Category 5 of new Narcotics Code, promulgated by Health Minister and the approval of Thailand’s Narcotics Control Board, paves the way to be allowed using non-narcotic cannabis components legally. In addition, cannabis is a medicinal plant that can be used for a variety of purposes such as fiber, oil and seed for consumption, therapy and relaxation, it is result in the widespread use of cannabis and cultivation. However, the obligations of the Single Convention on Narcotics of 1961, signed by Thai Government becomes the main problem toward the recreational use of cannabis. This study aims to review the concepts on Narcotics especially legal utilization of recreational cannabis use, the principle of international Narcotics laws and the foreign laws which allow the recreational cannabis use such as The Netherlands, Australian Capital Territory, and Indonesia. The results of the study are drawn into the analysis and the suggestions the proper way to measure the recreational cannabis use in Thailand.